Extensions of the CPA's Attest Function in Corporate Annual Reports. - Clarke, Robert W. (The Accounting Review, 1968)
The CPA's attest function has customarily involved primarily the rendering of opinions on financial statement presentations in reports to investors and creditors. Its principal application has been the expression of opinions on the fairness of the conventional financial statements included in corporate annual reports. The auditor's ability to verify information presented outside the financial statements would appear to be the primary determinant of whether his attest function could be extended to include that information. Verification is essentially a matter of obtaining sufficient evidence to provide a rational basis for judging the reliability of assertions made by others. The ability to obtain sufficient evidence to afford a reasonable basis for an opinion regarding any information, financial statement or otherwise, will vary, of course, depending upon circumstances in a particular examination and the professional competence and judgment of the auditor performing the examination. Some of the non-financial statement information is frequently presented for a period of two years or more. CPAs already render opinions in many cases on data covering two years or more. Before a CPA can render an opinion on a company's basic financial statements, he must determine whether those statements present fairly the company's financial position and results of operations.